Pengaruh Besaran Perekonomian, Tingkat Upah dan Inflasi Terhadap Kesempatan Kerja di Provinsi Jawa Timur Tahun 2014-2018 - Endah Kurnia Lestari; Sunlip Wibisono; Dimas Sa'bandianto (UPT Penerbitan Universitas Jember, 2022)
Labor is the driving force of the wheels of development. The number and composition of the workforce will continue to change along with the demographic process. Workers are residents with a minimum age limit of 15 years without a maximum age limit. Manpower development has many dimensions and is interrelated. The main problem in the development of the national manpower policy is the achievement of full employment and the improvement of the living structure of the community. The aim of this research is that the government is expected to focus more on developments (GRDP), especially in the manufacturing sector, which has a high rate of employment. The data used in this study is secondary data obtained from BPS and browsing internet websites as a support. While the method used in this research is panel data regression analysis method with REM method with the help of Eviews 9 software. The results of this study indicate that the GRDP variable (X1) has a significant and positive effect on TPAK, the Minimum Wage variable (X2) has a significant and negative effect. against TPAK. Employment opportunities in Java are influenced by 99.6% by HDI, GRDP, UMP and inflation while the remaining 0.4% is influenced by other factors.